2003
DOI: 10.1128/iai.71.5.2798-2809.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface-Exposed Loops ofHaemophilus influenzaeProtein P2 in the Mitogen-Activated Protein Kinase Cascade

Abstract: The outer membrane of gram-negative bacteria contains several proteins, and some of these proteins, the porins, have numerous biological functions in the interaction with the host; porins are involved in the activation of signal transduction pathways and, in particular, in the activation of the Raf/MEK1-MEK2/ mitogen-activated protein kinase (MAPK) cascade. The P2 porin is the most abundant outer membrane protein of Haemophilus influenzae type b. A three-dimensional structural model for P2 was constructed base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 79 publications
1
65
0
Order By: Relevance
“…Synthetic peptides, corresponding to the amino acid sequences of variable loop regions facing the cell exterior and thus more probably involved in the initial interaction with the host cell, proved to be able to activate the MEK1-MEK2/MAPK pathways similarly to the entire protein. In contrast, peptides modelled on internal β-strands were ineffective in inducing phosphorylation of such pathways (Galdiero, 2003c). A speculative scheme of signal transduction pathways involved in porin-mediated responses is depicted in Figure 4.…”
Section: Activation Of Eukaryotic Cell Signaling and Transcriptional mentioning
confidence: 99%
“…Synthetic peptides, corresponding to the amino acid sequences of variable loop regions facing the cell exterior and thus more probably involved in the initial interaction with the host cell, proved to be able to activate the MEK1-MEK2/MAPK pathways similarly to the entire protein. In contrast, peptides modelled on internal β-strands were ineffective in inducing phosphorylation of such pathways (Galdiero, 2003c). A speculative scheme of signal transduction pathways involved in porin-mediated responses is depicted in Figure 4.…”
Section: Activation Of Eukaryotic Cell Signaling and Transcriptional mentioning
confidence: 99%
“…With regard to other porins, one large loop (loop L3), folding back into the channel, determines effective pore cross section and consequent molecular exclusion limit, as well as its physiological and conductivity properties. 21 Recently, it has been demonstrated that porin P2 from Hib induces activation of signaling pathways in U937 cells through the MEK1-MEK2/MAPK cascade. 21,23,24 Peptide sequences corresponding to variable loop regions facing the cell exterior are able to activate this cascade and provide mitogen-activated protein kinase (MAPK) pathway activation similar to that of the entire porin.…”
Section: Introductionmentioning
confidence: 99%
“…Its molecular mass varies between 36 and 42 kDa, and it is present in all strains and functions as a porin. 22 P2 contains 16 anti-parallel β strands across the outer membrane, eight large loops of variable length on the external surface of the bacterial membrane, and eight short periplasmic turns 21 ( Figure 1A). All transmembrane regions are relatively conserved among strains, while considerable heterogeneity exists in loop regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations